1998
DOI: 10.1002/ijch.199800014
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Conformal CVD Diamond Films

Abstract: Abstract. A method for enhanced nucleation of diamond growth on non-diamond substrates is introduced via the results obtained in a wide variety of applications. The exact details of the method are still proprietary, but the outcome, as demonstrated in this paper, is unique and promises to be of great practical use. The main feature of the growth following the nucleation step is a very high density of nucleation sites which instantly started to grow over any structured surface in a perfectly conformal fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The process gave remarkably high, uniform, and conformal nucleation density over many materials, with the occasional lumps generated by residual large particles on the substrate. [46][47][48][49] 4 in H 2 ), the resultant films had remarkable properties, such as high Young's modulus and thermal diffusivity, which are dependent on the nucleation density, as will be discussed later. [50] Detailed investigations using synchrotron-based, near-edge X-ray absorption, fine-structure spectroscopy (NEXAFS) showed that NCD films grown using this seeding approach and growth chemistry are of very high quality, with greater than 99% sp 3 bonding.…”
Section: Historical Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The process gave remarkably high, uniform, and conformal nucleation density over many materials, with the occasional lumps generated by residual large particles on the substrate. [46][47][48][49] 4 in H 2 ), the resultant films had remarkable properties, such as high Young's modulus and thermal diffusivity, which are dependent on the nucleation density, as will be discussed later. [50] Detailed investigations using synchrotron-based, near-edge X-ray absorption, fine-structure spectroscopy (NEXAFS) showed that NCD films grown using this seeding approach and growth chemistry are of very high quality, with greater than 99% sp 3 bonding.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Many techniques have been used including the polishing of the substrate with diamond powder, ultrasonic treatment of the substrate in a slurry of micrometer or smaller sized diamond powder, coating of the substrate with diamond-containing materials, or the precoating of the substrate with carbon materials which, when exposed to the diamond growth environment, convert to nuclei of crystalline diamond. [27,44,45,48,49] After nucleation, the individual nuclei grow three dimensionally until they coalesce to form a continuous film. Often some degree of non-diamond carbon is incorporated during this nucleation and coalescence stage.…”
Section: Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Philip et al 66 used DNDs to seed silicon substrates and were able to get coalesced diamond lms. They used a combinatorial technique developed by Rotter and coworkers (discussed later) 67,68 to seed their substrates. Fig.…”
Section: Electrostatic Seedingmentioning
confidence: 99%
“…Plasma treatments have also been used in the past on other surfaces to facilitate electrostatic seeding. [98][99][100][101][102][103] This should not be confused with the combinatorial seeding technique (discussed later) 67,68,104 in which a thin carbon layer is formed on the substrate before electrostatic seeding. The measured z-potential of any surface gives the average over certain area or certain volume of liquid at a given pH.…”
Section: Electrostatic Seedingmentioning
confidence: 99%